Lend Global, Fund Local? Price and Funding Cost Margins in Multinational Banking - Galema, Rients; Koetter, Michael; Liesegang, Caroline (Review of Finance, 2016)
Abstract In a proposed model of a multinational bank, interest margins determine local lending by foreign affiliates and the internal funding by parent banks. We exploit detailed parent-affiliate-level data of all German banks to empirically test our theoretical predictions in pre-crisis times. Local lending by affiliates depends negatively on price margins, the difference between lending and deposit rates in foreign markets. The effect of funding cost margins, the gap between local deposit rates faced by affiliates abroad and the funding costs of their parents, on internal capital market funding is positive but statistically weak. Interest margins are central to explain the interaction between internal capital markets and foreign affiliates lending.